Abnormal diurnal variation in salt and water excretion in patients with obstructive sleep apnoea. - Warley, A; Stradling, JR (1988)
1. In healthy individuals, sleep is associated with a fall in urine and sodium output. 2. Seven male patients with obstructive sleep apnoea exhibited a paradoxical rise in both urine and sodium output during the hours of sleep. 3. Continuous positive airway pressure applied via the nose abolished both the apnoea and the nocturnal rise in urine and sodium output, thereby restoring the diurnal pattern towards normal.